Everyday Activities for Children with Mitochondrial Disorder: A Retrospective Chart Review - Marieke Lindenschot; Imelda J. M. de Groot; Saskia Koene; Ton Satink; Esther M. J. Steultjens; Maria W. G. Nijhuis-van der Sanden (Occupational Therapy International)
Background. Engagement in everyday activities is important for the health and wellbeing of children. Children with mitochondrial disorders have impaired energy production leading to limitations in activity. It is unknown which activities these children perform and if the nature of activities of low-functioning children differs from average-functioning children. Therefore, this pilot study explored the activities reported in patient records of a heterogeneous group of children with genetically confirmed mitochondrial disorders. Methods. A retrospective qualitative directed content analysis by health care professionals reported activities (as part of their professional reasoning obligations) in hospital patient records of children with mitochondrial disorder. Results. Seventeen patient records, presenting notes on capacities and performed activities, showed an overview of everyday activities that covered the categories: self-care, house chores, therapy, school, computing, hobby, play, sports, and mobility/transport. The activity categories of low-functioning children did not differ from average-functioning children, although descriptions of specific activities differed between groups. Conclusion. This pilot exploration indicates that the types of activities that children with mitochondrial disorders perform are not necessarily linked to the child’s impairments. However, differences in levels of independence, assistive device usage, and energy costs seem to exist. Future research should address the child’s perspective on, and meaning of, activity performances.